Pengaruh Penerapan E-Ticket terhadap Kepuasan Konsumen PT ASDP Indonesia Ferry (Persero) Cabang Pelabuhan Kamal - Aqidatul Annisa; Ika Lis Mariatun; Yusrianto Sholeh (J-MAS (Jurnal Manajemen dan Sains), 2023)
The basis of this research is the change in service that is felt by changes in payments made by electronic payments to get e-tickets at the port branch of PT ASDP Indonesia Ferry (Persero) Kamal Bangkalan, currently PT. ASDP's policy in deploying e-tickets is to change the system from using manual tickets to e-tickets, so that during the implementation process there are still complaints and dissatisfaction from passengers in using the e-ticket service. consumers have a need to learn. The question posed in this study is whether the quality of information and service systems can have a positive effect on passenger satisfaction. on passengers. satisfaction when using PT. ASDP Indonesia Ferry (Persero). This study uses a quantitative approach to the type of field research. The object of this research is the consumers of PT ASDP Ferry Indonesia (Persero), namely through passengers who use e-ticketing services. Sampling was done by simple random sampling technique with 30 samples as respondents. The data used in this study are primary data obtained from distributing questionnaires. Methods of data analysis in this study used research instrument tests, classical hypothesis testing, multiple linear regression tests, t-statistical tests and F-statistical tests, analyzed using SPSS20 software and Microsoft Excel 2010. The results also showed that system quality, information quality and service quality has a positive and significant effect on consumer satisfaction in using the e-ticketing service of PT ASDP Indonesia (Persero) Ferry. Partially, system quality (X1) has a positive and significant effect on information quality (X2) and service quality (X3) has a positive and significant effect on passenger satisfaction (Y) PT. ASDP Indonesia Ferry (Persero) uses an online ticket service system.